Condition-based maintenance for a multi-component system subject to heterogeneous failure dependences - Zhao, Yixin; Cozzani, Valerio; Sun, Tianqi; Vatn, Jørn; Liu, Yiliu (Reliability engineering & system safety, 2023)
•A new framework to evaluate heterogeneous failure dependences.•A generalized CBM model for systems with heterogeneous failure dependences.•Verification of the model with a subsea transmission system. Many industrial facilities consisting of multiple components are prone to failure interactions and degradation interactions. In such systems, these interactions are frequently characterized by failure dependences that may accelerate the degradation of components. Due to system layout and functional interactions, not all components have the same failure dependence. In the general context of complex failure dependences in dependent multi-component systems, heterogeneous failure dependences further complicate the maintenance activities during operation. The present study developed a comprehensive framework for evaluating heterogeneous failure dependences and a maintenance optimization model by Markov processes for multi-component systems. The proposed method is applied to a practical case consisting in a parallel subsea transmission system to illustrate the effects of heterogeneous failure dependences. The results show that the heterogeneous failure dependences framework and the maintenance model guide the optimization of maintenance strategies to maximize the system availability and minimize the maintenance cost.